Investigating the Effect of Valve Shape on Anti-Lock Braking System Plunger Pump Performance Using Fluid-Structure Interaction Simulation - Mo, Jang-oh; Choi, Jae-Hyuk (International journal of automotive technology, 2021)
An anti-lock braking system (ABS) is an anti-skid braking system commonly used as a safety feature in vehicles. The hydraulic control unit for the ABS of a vehicle includes a plunger pump between the wheel and master cylinder. This paper presents numerical investigations of the effect of valve shapes on the performance improvement provided by a plunger pump, focusing on two different valve shapes, ball-type and hat-type. Transient laminar flow analyses of plunger pumps with ball and hat-type inlet valves are performed under motor speeds from 1000 to 5000 rpm using the fluid-structure interaction (FSI) and user-defined function (UDF) techniques. An experimental verification of the simulation results for the plunger pump with a ball-type valve was conducted using the standard pump test of the Mando Corporation, South Korea. A comparison of the simulation and experimental results suggests that these are in good agreement. The simulation results indicate that the hat-type valve outperforms the ball-type valve due to a shorter delay in the closing time at the end of the suction cycle. These findings suggest that valve shape has a considerable impact on the performance improvement provided by a plunger pump, providing crucial insights into the future design of high-efficiency pumps.